Closed chamber measurements of net ecosystem exchange of CO2 from Siikaneva bog, Finland: 2012-2014 - Korrensalo, Aino; Tuittila, Eeva-Stiina; Uljas, Salli (In supplement to: Korrensalo, Aino; Mehtätalo, Lauri; Alekseychik, Pavel; Uljas, Salli; Mammarella, Ivan; Vesala, Timo; Tuittila, Eeva-Stiina (2019): Varying Vegetation Composition, Respiration and Photosynthesis Decrease Temporal Variability of the CO2 Sink in a Boreal Bog. Ecosystems, https://doi.org/10.1007/s10021-019-00434-1, 2019)
The datasets contains the chamber CO2 measurement and leaf area data of years 2012-2014 used in fitting the non-linear model.
Keywords: bog; Carbon; carbon dioxide; Eddy covariance; net ecosystem exchange; Peatland; Photosynthesis; Respiration; Vegetation